Finansowanie innowacji produktowych a komunikacja marketingowa na przykładzie firmy Tesla Inc. - Cuda, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Barriers to entry into the automotive industry are absolute high ‒ only the biggest companies can afford a high capital investment. However, the small California startup proved that entering into this hermetic branch is possible. Tesla Inc. is one of the most innovative companies in the world ‒ despite its short history, it has revolutionized automotive industry and spurred the biggest game players into the action related with implementation of electrical drive innovations. Tesla’s success is the result of the unusual marketing strategy, that is not typical for its branch but, most of all, turned out to be effective in increasing capital volume and implementing innovations.
Keywords: marketing; innovations; EV; electric vehicles